competences required by graduates of the medicine program according to the thought of authorities and teachers (Revista Electrónica REDINE, 2018)
The gone away one(graduated one) from the university and specifically of the program of medicine of the UCLA, must rely on competitions that they should qualify it to exercise successfully this profession. The present investigation was realized to know the thought of authorities and teachers in relation with the competitions needed for gone away (graduated) from the Program of Medicine of the University Centroccidental "Lisandro Alvarado" (UCLA). It was developed by base in the qualitative paradigm and an approach interpretativista, by currents hermeneutics and fenomenología. The information was tried by means of the comparative constant method proposed by Glaser and Strauss (9). The key informants were constituted by an intentional sample of authorities and teachers of the Program of Medicine of the UCLA, who were approached by means of the interview in depth. The obtained information was analyzed, labelled, categorized and interpreted with the intention of achieving a process of conceptualization and theoretical propositions like synthesis. There was generated a theory that allowed to understand and to describe the competitions that there must exhibit the graduated one from medicine of the UCLA, according to the expressed for the informants.
Keywords: medical education; skills development; medical graduates; competencies; medical training